Imperial encounters : the politics of representation in North-South relations - Doty, Roxanne Lynn (Borderlines (Minneapolis, Minn.), 1996)
"Developed/underdeveloped," "first world/third world," "modern/traditional"although there is nothing inevitable, natural, or arguably even useful about such divisions, they are widely accepted as legitimate ways to categorize regions and peoples of the world. In Imperial Encounters, Roxanne Lynn Doty looks at the way these kinds of labels influence North-South relations, reflecting a history of colonialism and shaping the way national identity is constructed today.